2015
DOI: 10.5194/ms-6-81-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gear loss factor on the power loss prediction

Abstract: Abstract. In order to accurately predict the power loss generated by a meshing gear pair the gear loss factor must be properly evaluated. Several gear loss factor formulations were compared, including the author's approach.A gear loss factor calculated considering the load distribution along the path of contact was implemented.The importance of the gear loss factor in the power loss predictions was put in evidence comparing the predictions with experimental results. It was concluded that the gear loss factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As illustrated, the model (1) consists of an electric motor, a torque sensor (3), gears and a coupling. The measurement model has two pairs of gears, a torque sensor is installed in the system's input shaft, a variable-speed electric motor drives the entire system and digital indicator (2). In one of the couplings, the two gears are divided into two parts for coupling with no relative movement between the two halves when working.…”
Section: Experimental Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated, the model (1) consists of an electric motor, a torque sensor (3), gears and a coupling. The measurement model has two pairs of gears, a torque sensor is installed in the system's input shaft, a variable-speed electric motor drives the entire system and digital indicator (2). In one of the couplings, the two gears are divided into two parts for coupling with no relative movement between the two halves when working.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…To calculate these losses, one must know the loads in every contributing machine element. A literature review [1][2][3][4][5] indicates that the sources of power loss are divided into load-dependent and load-independent components. The load-dependent power losses are the tooth friction and bearing friction, while the load-independent ones are the friction in the contact seals and the losses due to oil churning, windage, and oil squeezing during gear meshing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Mao's FD model, the finite element (FE) model is also commonly implemented. Fernandes et al 10,11 predicted the maximum meshing temperature of POM gears via a semi-analytical method. They analytically calculated the frictional heat with a power loss model and numerically simulated the heat transfer process of generated frictional heat.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the rotational speed has an influence on meshing time and the operating trapped fluid. Fernandes [12] have studied load distribution along the length of path of contact to estimate gear loss factor and its influence on power loss prediction and concluded that the classical formulas are accurate in some specific condition. Luis magalhaes et al, [13] have studied influence of tooth profile and oil formation on power loss.…”
Section: Introductionmentioning
confidence: 99%